ANALISIS PENGANGKATAN PONTOON P20T MENGGUNAKAN MOBILE CRANE 50T DI PT WEIR MINERALS INDONESIA - Astin Eka Wahyuni; Komeyni Rusba; James Everd Adolf Liku (LPSDI Bina Patria, 2024)
PT Weir minerals is one of the companies engaged in dewatering, one of which is the Multiflo Pump, this pump requires buoyancy to be used with the help of a Pontoon before it can be used on the water. Before the pontoon can be placed in the specified location, a lifting process needs to be carried out, the lifting process is the process of moving a lifting object from one place to another in a systematic and planned manner. The lifting process is carried out to move the pontoon on the Tronton to be taken to a location. The method used for this lifting process is to use the help of a mobile crane type conveyance aircraft with a capacity of 50T on a 20 Ton pontoon and a bridle hitch binding technique on 4 parts. The results of the analysis of the pontoon lifting process with a weight of 20T can be done using a 50T mobile crane. By using a 50T crane, the poonton weighing 20T can be lifted with a maximum angle of 60 degrees